Operas in English: A Dictionary - Griffel, Margaret Ross (Rowman & Littlefield Publishers, 2012)
Although many opera dictionaries and encyclopedias are available, very few are devoted exclusively to operas in a single language. In this revised and expanded edition of Operas in English: A Dictionary, Margaret Ross Griffel brings up to date her original work on operas written specifically to an English text (including works both originally prepared in English, as well as English translations). Since its original publication in 1999, Griffel has added nearly 800 entries to the 4,300 from the original volume, covering the world of opera in the English language from 1634 through 2011. Listed alphabetically by letter, each opera entry includes alternative titles, if any; a full, descriptive title; the number of acts; the composer’s name; the librettist’s name, the original language of the libretto, and the original source of the text, with the source title; the date, place, and cast of the first performance; the date of composition, if it occurred substantially earlier than the premiere date; similar information for the first U.S. (including colonial) and British (i.e., in England, Scotland, or Wales) performances, where applicable; a brief plot summary; the main characters (names and vocal ranges, where known); some of the especially noteworthy numbers cited by name; comments on special musical problems, techniques, or other significant aspects; and other settings of the text, including non-English ones, and/or other operas involving the same story or characters (cross references are indicated by asterisks). Entries also include such information as first and critical editions of the score and libretto; a bibliography, ranging from scholarly studies to more informal journal articles and reviews; a discography; and information on video recordings. Griffel also includes four appendixes, a selective bibliography, and two indexes. The first appendix lists composers, their places and years of birth and death, and their operas included in the text as entries; the second does the same for librettists; the third records authors whose works inspired or were adapted for the librettos; and the fourth comprises a chronological listing of the A–Z entries, including as well as the date of first performance, the city of the premiere, the short title of the opera, and the composer. Griffel also include a main character index and an index of singers, conductors, producers, and other key figures.